PRINSIP-PRINSIP TAZKIYAH AL-NAFS DALAM ISLAM DAN HUBUNGANNYA DENGAN KESEHATAN MENTAL - Masyhuri Masyhuri (An-Nida', 2012)
Tazkiyah al-nafs according to language meaning means Soul cleanliness, self cleanlines. Tazkiyah al-nafs is one of methodes in soul develoving and human akhlak education. Epistemologically, tazkiyah al-nafs has two meaning “cleanliness and curative treatment. Termologically, it means soul sanctification from all of disease by using asma Allah to become his akhlak (takhalluq) which at the end tazkiyah means tathahhur, tahaqquq, and takhalluq. The porpuses of the study are: 1. To know the consept of tazkiyah al-nafs and relationship with mental health, 2. To participate in exploring and developing Islamic studies to become mind share in overcoming soul crisis that surge humna lives nowadays.